Neonatal brachial plexus injuries and their impact on growing bone. An experimental study. Issue 12 (December 2020) - Gkiatas, Ioannis; Kostas-Agnantis, Ioannis; Batistatou, Anna; Kosmas, Dimitrios; Korompilia, Maria; Gelalis, Ioannis; Pakos, Emilios; Vekris, Marios; Korompilias, Anastasios
Highlights: Denervation provokes structural changes to the bone. Bone density is affected mostly in the trabecular site. Early microsurgical intervention may result in better. outcomes. Abstract: Neonatal brachial plexus palsy remains a problem, even in light of current advances in perinatal care. While many cases resolve spontaneously, the concern remains on the best means of surgical management for restoration of elbow flexion and shoulder reanimation. The present experimental study in an animal model examines the evidence that supports that neonatal brachial plexus injuries result in structural changes in the affected bone. The study suggests that if the microsurgical reinnervation takes place early enough, these changes may be diminished. On the other hand there is no way to identify at birth, which injuries will be permanent and will need surgical repair and which will spontaneously improve.